Qualitative and quantitative interpretation of SEM image using digital image processing - SALADRA, DAWID; KOPERNIK, MAGDALENA (Journal of microscopy (Oxford), 2016)
Summary The aim of the this study is improvement of qualitative and quantitative analysis of scanning electron microscope micrographs by development of computer program, which enables automatic crack analysis of scanning electron microscopy (SEM) micrographs. Micromechanical tests of pneumatic ventricular assist devices result in a large number of micrographs. Therefore, the analysis must be automatic. Tests for athrombogenic titanium nitride/gold coatings deposited on polymeric substrates (Bionate II) are performed. These tests include microshear, microtension and fatigue analysis. Anisotropic surface defects observed in the SEM micrographs require support for qualitative and quantitative interpretation. Improvement of qualitative analysis of scanning electron microscope images was achieved by a set of computational tools that includes binarization, simplified expanding, expanding, simple image statistic thresholding, the filters Laplacian 1, and Laplacian 2, Otsu and reverse binarization. Several modifications of the known image processing techniques and combinations of the selected image processing techniques were applied. The introduced quantitative analysis of digital scanning electron microscope images enables computation of stereological parameters such as area, crack angle, crack length, and total crack length per unit area. This study also compares the functionality of the developed computer program of digital image processing with existing applications. The described pre‐ and postprocessing may be helpful in scanning electron microscopy and transmission electron microscopy surface investigations. Lay description Micrographs of scanning electron microscopy obtained from micromechanical tests performed for athrombogenic titanium nitride/gold coatings deposited on polymeric substrates applied in pneumatic ventricular assist devices are present in large numbers due to a multistage character of the micromechanical testing. Anisotropic surface defects observed in the SEM micrographs require support for qualitative and quantitative interpretation. Improvement of qualitative analysis of scanning electron microscope results was proposed by a computer program for image processing, which uses image processing algorithms. Authors proposed several modifications of the known image processing techniques and also applied combinations of the selected image processing techniques. Introduced quantitative analysis of digital scanning electron microscope results enables computation of the selected stereological parameters. The study also compares the functionality of developed computer program of digital image processing with existing applications.